Performance of Brazilian students of elementary school from public and private school in the evaluation of the letter identification and the lexical process tests - de Oliveira, Adriana Marques [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2015)
This study aimed to describe, to compare and to correlate the performance of Brazilian students from the 2nd to the 5th grade of school in public and private institutions in tests of letter identification and lexical process evaluation. 262 students attending elementary school from Marilia, Sào Paulo, Brazil participated in this study. 122 students from public school, distributed as follows: G1 - 24 students of the 2nd grade level, G2 -33 students of the 3rd grade level, G3 - 31 students of the 4th grade level, G4 - 34 students of the 5th grade level. 140 students from private schools subdivided into: G5 - 37 students of the 2nd grade level, G6 - 34 students of the 3 rd grade level, G7 - 34 students of the 4th grade level, and G8 - 35 students of the 5th grade level. The students were assessed by both the Letter Identification process and the Lexical process: (1) Sound and letter identification, (2) Same-Different, (3) Lexical decision, (4) Word reading, (5) Nonword reading and (6) Word and nonword reading from the Brazilian adaptation of the assessment of the reading processes - PROLEC. The results suggest evidence that the students from public and private schools differ in the assessed tests. The exception is the lexical decision test for the 2nd grade, same-different test for the 4th grade and test of letter, same-different, lexical decision and high frequent word reading for the 5th grade. A better performance among students from private school is noticed when compared to that from public school. Independently of the school institution, evidence of association among the students of 2nd and 3rd grade level is noticed in the following tests: letter (L) and sound (S), letter (L) and word reading (WR), letter (L) and nonword reading (NWR), sound (S) and word reading (WR), sound (S) and nonword reading (NWR), and word reading (WR) and nonword reading (NWR). Among the students from the 4th grade, there was an evidence of association between the tests L and S, L and WR, L and NWR, S and WR, WR and NWR. These findings showed that the evidence of difference is higher among the students until the 4th grade, due to the higher use of the phonological route by these students. This highlights the difference at teaching the alphabetic principle of Portuguese in the learning system in private and public schools. The tests which presented no evidence of difference among the 5th grade level students are the ones that the reading by the phonological route is not entirely required. These words could be read by the lexical route. The findings of this study are important to help the educators and the professionals in the educational and health area identify the students with difficulties in each grade level. Thus, assisting the teaching planning of the alphabetic principle during the literacy acquisition independently of being a public or a private school.
Keywords: elementary school; evaluation; learning; Reading processes